Gestión de proyectos con enfoque PMI para mejorar ell desempeño empresarial de M y P García Constructoraa S.A.C Trujillo 2021 - Milla Rodriguez, Zulema Pilar (2021)
The present investigation was carried out with the objective of demonstrating that through the implementation of projects with a PMI approach, the business performance of M y P García Constructora can be significantly improved, a company in the construction sector that in recent years despite having increased its number of clients and executed projects, has shown a decrease in its performance, the latter defined in three indicators: efficiency, effectiveness and real utility with respect to the projected utility. In this sense, project management with a PMI approach was implemented for the "Construction of commercial premises" project, in this project planning formats and processes, monitoring and control flows were standardized that allowed timely and timely decisions to be made, making use of project management tracking tools such as the earned value tool. At the end of the project, a favorable result was obtained, showing that the project management variable with a PMI approach significantly improved the business performance of M y P García Constructora. The executed project obtained an increase of 19% in the efficiency indicator, 12% in the efficiency indicator and 0.5%, that is, an additional S/ 6,454.08 in the real profit compared to the average values obtained in the projects executed before the implementation of the project management methodology with a PMI approach. All this was perfected thanks to the standardization of processes, exhaustive forecasting and good monitoring carried out throughout the entire project.